DEVELOPMENT OF AN AGE-PERIOD-COHORT-EXPERIENCE MODEL FOR FILIPINO INTERGENERATIONAL DIVERSITY INQUIRY IN SCHOOLS - Bongco, Roxanne (Trường Đại học Đà Lạt, 2024)
The purpose of this study is to develop a model to scrutinize intergenerational (IG) diversity in the workplace in response to current issues in IG diversity studies. These include the ambiguity of the definition of generation as the basis for understanding IG diversity and the overgeneralization of findings that could lead to generational stereotypes. The present study consists of two-phase developmental research. Phase One involved model development based on an integrative literature review. Phase Two focused on the validation of the model in the context of multigenerational colleagues in Philippine basic education schools. An Age-Period-Cohort-Experience (APCE) model was developed to explore IG diversity in the workplace. Validation showed the applicability of the model to obtain a contextualized understanding of IG diversity through the recognition of the overlapping and interrelated effects of age, period, cohort, and work experiences. The APCE model provided a useful lens for scrutinizing the IG diversity of the teachers in the workplace through qualitative research with limitations in terms of their age, period, cohort, and experiences. As such, said descriptions for each generation could only hold true while all four conditions are present. Until a strong basis for analysis is established, the separation of one effect from another will be difficult.